Motivational Differences between Whole Blood and Apheresis Donors in Quebec, Canada: A Questionnaire-Based Survey in a Voluntary Nonremunerated Context. (29th July 2015) - Charbonneau, Johanne; Cloutier, Marie-Soleil; Carrier, Élianne
Abstract : Background . Finding ways to recruit apheresis donors is crucial. The aim of this study was to provide a quantitative analysis of the motivations of regular plasma/platelets donors (PPDs) in comparison with those of regular whole blood donors (WBDs), in a voluntary and nonremunerated context. Study Design and Methods . Motives to donate blood and demographic characteristics were collected through questionnaires completed by 795 WBDs and 473 PPDs. Chi-square tests were completed to determine which motivations stand out across the two blood donor groups. Results . The motivator selected by the highest percentage was "my blood can save lives." Comparison of WBDs and PPDs showed that 12 out of 23 items were statistically significantly different from one group to another. Conclusion . The belief that helping others is in their nature is more prevalent among PPDs. In this sense, their profile is unique. Four other motivators distinguish this group from the WBDs: "I think there is a strong need for blood products, " "it gives me a sense of pride, " "I like to have goals, " and "I receive telephone reminders." These motivators point to the role the ongoing support provided by blood collection agencies (BCAs) plays with PPDs.